2017
DOI: 10.1111/jvim.15025
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heat‐treatment on Accuracy of Infrared Spectroscopy and Digital and Optical Brix Refractometers for Measuring Immunoglobulin G Concentration in Bovine Colostrum

Abstract: BackgroundHeat‐treatment of colostrum is a method developed to reduce calf exposure to pathogens. Infrared (IR) spectroscopy and Brix refractometers can be used for measuring colostral IgG concentration and assessing colostrum quality.ObjectivesTo determine the impact of heat‐treatment on accuracy of IR spectroscopy and Brix refractometers for measuring colostral IgG concentration and assessing colostrum quality before and after heat‐treatment.AnimalsA total of 60 Holstein dairy cows on 8 commercial dairy farm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 35 publications
(82 reference statements)
1
31
1
1
Order By: Relevance
“…Contrary to our study results, Morrill et al (33) reported a higher concentration of IgG in colostrum ranging from <1 to 200 mg mL -1 with a mean of 68.8 mg mL -1 and 30% of colostrum containing <50 mg mL -1 of IgG. On the other hand, a 72.91 mg mL - Determining the cut-point level for good quality colostrum by means of the Brix refractometer was previously studied (15,35,36,34,38). Our cut-point level of good quality colostrum was determined at ≥20% Brix corresponding to IgG concentration ≥50 mg mL -1 of colostrometer results.…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…Contrary to our study results, Morrill et al (33) reported a higher concentration of IgG in colostrum ranging from <1 to 200 mg mL -1 with a mean of 68.8 mg mL -1 and 30% of colostrum containing <50 mg mL -1 of IgG. On the other hand, a 72.91 mg mL - Determining the cut-point level for good quality colostrum by means of the Brix refractometer was previously studied (15,35,36,34,38). Our cut-point level of good quality colostrum was determined at ≥20% Brix corresponding to IgG concentration ≥50 mg mL -1 of colostrometer results.…”
Section: Discussioncontrasting
confidence: 89%
“…Similarly, no change in IgG concentration was observed when colostrum was treated at 60°C for 60 min using a commercial on-farm batch pasteurizer (43). Interestingly, similar to our findings, colostrum containing > 50 mg mL -1 and cows was carried out at 63°C for 30 min, 60°C for 60 min and 72°C for 15 s where no effect on the IgG concentration and viscosity of colostrum was observed at 60°C for 60 min compared to a study where no impact on IgG concentration and quality of colostrum treated at 60°C and 63°C for 30 and 60 min was observed (38,45).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our cut-point level of good quality colostrum was determined at ≥ 20%Brix corresponded to ≥ 50 mg mL -1 IgG concentration using colostrometer. Chigerwe et al (11) and Bielmann et al (25) suggested 22%Brix as an optimal cut-point level as compared to the recommended levels (18%, 21% and 23%) for Jersey dairy cattle colostrum (6,13,(23)(24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…Three thermal treatments (60 °C/60 min, 63.5 °C/30 min and 72.0 °C/15 sec) were performed in a water bath to determine the cut-point temperature that may impact on the viscosity in relation to the IgG concentration (12,13). The water bath was calibrated and adjusted to ± 0.5 °C with an additional digital thermometer (Testo 112 Type NTC, Germany) and thermometer type UT330A (Reichelt Elektronik, Germany).…”
Section: Thermal Treatmentsmentioning
confidence: 99%